Analisis Word Of Mouth Dan Brad Image Terhadap Keputusan Pembelian Smartphone Di Kota Sukabumi - Seira Aryatilandi; Asep Muhammad Ramdan; Erry Sunarya (JMD : Jurnal Riset Manajemen & Bisnis Dewantara, 2020)
Abstract The purpose of this study is to measure how much influence word of mouth and brand image have on purchasing decisions. The variables used in this study are word of mouth,, brand image, and purchasing decisions. The method used in this research is to use probability sampling by distributing questionnaires as many as 150 respondents to consumers who use Iphone smatphone in Sukabumi City. Data analysis technique used is multiple linear regression where in this method the method of partial effect and simultaneous influence is used. The results obtained show that there is no positive and significant influence between word of mouth on purchasing decisions. And there is a positive and significant influence between brand image on purchasing decisions.